Parkinson’s disease in the Lebanese population: knowledge and attitude scales’ validation and correlates - Soula Abramian; Samah Tawil; Marwan Akel; Chadia Haddad; Pascale Salameh (BMC Public Health)
Abstract Background Parkinson’s disease (PD) is a progressive degenerative neurological disorder that negatively affects the quality of life of affected individuals as well as their care givers. There is limited information in both epidemiological data and awareness level on PD in the Middle East. Considering the increasing prevalence of PD, the lack of awareness and negative attitudes toward PD pose a barrier in the provision of appropriate care for individuals with PD. Objective This study aimed to validate scales to explore the knowledge and attitude towards PD among the general population in Lebanon and identify the associated factors related to the knowledge and attitude assessment. This study’s results would guide awareness strategies in the country including public health strategies, campaigns and education sessions for the general population as well as targeted people. Methodology An online cross-sectional study was conducted between July and September 2023 in Lebanon. Snowball sampling was used to recruit 400 Lebanese adults living in Lebanon. The validity and reliability of the knowledge and attitude scales were assessed, followed by a thorough statistical analysis to explore the factors associated with these scales. Results The knowledge and attitude scales generated by this study were valid and reliable; Cronbach’s alpha values for knowledge and attitude scales were 0.697 and 0.901, respectively. Using these scales, 91.8% demonstrated inappropriate knowledge and 93% showed positive attitude towards PD. Higher knowledge scores were significantly associated with female gender (Beta = 1.130), being a healthcare professional (Beta = 2.514), having heard about PD (Beta = 5.338), obtaining the source of information from electronic databases (Beta = 1.283), from pharmacist or physician (Beta = 1.212), from personal readings (Beta = 2.386), and having PD or knowing someone with PD; a friend or a family member (Beta = 1.179). However, being illiterate or having primary or secondary education (Beta = -0.874), having a higher household crowding index (Beta = -1.890), not knowing if contents from sources provide negative images about PD (Beta = − 1.908) and preferring not to say to which social class they belong (Beta = − 1.602) were significantly associated with lower knowledge scores. Believing that contents from sources provide negative images about PD (Beta = 8.246) was significantly associated with a higher attitude score, i.e., a more negative attitude towards PD. Conclusion This study showed low levels of knowledge and an overall positive attitude towards PD in Lebanon. Factors associated with higher knowledge and attitude scores, including gender, education level, profession, knowing someone with the disease, household crowding index, social class, source of information and contents of such sources, reflect the need to consider those when implementing targeted corrective actions. Future studies can focus on educational campaigns to improve public awareness, reduce misconceptions and limit barriers to the early diagnosis and provision of optimal care to the affected patients.